Impact of cooperative learning on teamwork competence. Issue 1 (4th March 2019) - Hebles, Melany; Yaniz-Álvarez-de-Eulate, Concepción; Jara, Mauricio
Abstract : Purpose: The purpose of this paper is to analyze the impact of a classroom application of the cooperative learning (CL) methodology on nine dimensions of business students' teamwork competence (TC). Design/methodology/approach: The authors used a quasi-experimental pre-post design with a previous cohort as control group (first-year students from the year prior to treatment application), applying treatment to a sample of 228 first-year students in a School of Economics and Business at a Chilean University (114 as treatment and 114 as control). Findings: The authors' results show that CL had a positive, significant influence on five dimensions of TC: collective efficacy, planning, goal setting, problem solving and conflict management. Research limitations/implications: This paper upholds the importance and effectiveness of CL in developing TC. However, the evidence suggests that the effectiveness of the CL methodology was limited to development and improvement of less complex dimensions of TC. More complex dimensions require a longer period of time to be developed. Practical implications: This research is an important contribution to the design and implementation of appropriate methodologies for developing a widely needed area of competence in the workplace, considering its multidimensional nature, whether in academia or business. Originality/value: This is the first study to seek empirical evidence that would link the CL methodology with TC. In addition, it fills a gap in the literature on the development of TC in its multiple dimensions. It particularly addresses the training of business professionals. Abstract : Propósito: El objetivo principal de este trabajo es analizar el impacto de la metodología Aprendizaje Cooperativo aplicada en aula en nueve dimensiones de la Competencia Trabajo en Equipo en estudiantes de negocios. Diseño/Metodología/Enfoque: Se ha empleado un diseño cuasi experimental pre-post test con grupo cuasi control en una cohorte anterior (curso de primer año del año previo a la aplicación del tratamiento), aplicada a 228 estudiantes de 1° año de una Facultad de Economía y Negocios de una Universidad Chilena (114 de tratamiento y 114 de control). Resultados: Los resultados obtenidos ponen de manifiesto un efecto positivo y significativo de la metodología Aprendizaje Cooperativo sobre cinco dimensiones de la Competencia Trabajo en Equipo, las cuales son eficacia colectiva, planificación, establecimiento de objetivos, resolución de problemas, y gestión de conflictos. Limitaciones/Implicancias: El presente trabajo sostiene la importancia de emplear una metodología de Aprendizaje Cooperativo en la formación de la Competencia Trabajo en Equipo. No obstante, la evidencia presentada sugiere que la aplicación de la metodología Aprendizaje Cooperativo es significativa para dimensiones de menor complejidad en su desarrollo, ya que aquellas más complejas requieren de un horizonte más largo para ser adquiridas. Implicancias prácticas: Esta investigación supone una contribución importante para el diseño e implementación de metodologías adecuadas para la formación de una competencia ampliamente requerida en el mundo profesional, considerando su carácter multidimensional, tanto en el ámbito universitario como empresarial. Originalidad/Valor: Es el primer estudio que busca evidencia empírica acerca de la relación entre la aplicación de una metodología de Aprendizaje Cooperativo y la Competencia Trabajo en Equipo. Adicionalmente, complementa un vacío en la literatura a la formación de la Competencia Trabajo en Equipo desde sus múltiples dimensiones. En especial, en la formación de profesionales de los negocios.